2017
DOI: 10.1016/j.biocon.2017.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Using Bayesian mark-recapture modelling to quantify the strength and duration of post-release effects in reintroduced populations

Abstract: Translocated animals often suffer elevated mortality during some acclimation period after release. Such post-release effects must be accounted for when estimating normal survival rates and therefore predicting population persistence. The standard approach for doing this is to nominate a fixed acclimation period, and either i) exclude survival data over that period, or ii) use model selection criteria to test whether survival differs over that period. We present a more flexible approach where the acclimation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
0
52
2
Order By: Relevance
“…The BP population declined over the first 2 years due to poor initial survival of the reintroduced females (only four of 21 females survived the first 6 months), but modeling projections suggested that this was due to transient effects of the translocation (cost of release effects; Armstrong et al, 2017) and that more stable site based vital rates would allow the population to persist (Panfylova, Bemelmans, Devine, Frost, & Armstrong, 2016). The 44 birds released were from Tiritiri Matangi (TM) Island, which is currently considered the only possible source population.…”
Section: The Decision Problemmentioning
confidence: 99%
“…The BP population declined over the first 2 years due to poor initial survival of the reintroduced females (only four of 21 females survived the first 6 months), but modeling projections suggested that this was due to transient effects of the translocation (cost of release effects; Armstrong et al, 2017) and that more stable site based vital rates would allow the population to persist (Panfylova, Bemelmans, Devine, Frost, & Armstrong, 2016). The 44 birds released were from Tiritiri Matangi (TM) Island, which is currently considered the only possible source population.…”
Section: The Decision Problemmentioning
confidence: 99%
“…For example, survival immediately following the release of animals into new habitat affects the outcome of a relocation (i.e., establishment phase, Armstrong and Seddon , Armstrong et al. ). Reduced survival during the establishment phase occurs in a range of vertebrates (birds [Armstrong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced survival during the establishment phase occurs in a range of vertebrates (birds [Armstrong et al. ], mammals [Jule et al. ], reptiles [Roe et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations